Antileishmanial Activity and Influence on Mitochondria of the Essential Oil from Tagetes lucida Cav. and Its Main Component - Lianet Monzote; Yamilet Gutiérrez; Laura Machin; Katrin Staniek; Ramón Scull; Prabodh Satyal; Lars Gille; William N. Setzer (MDPI AG, 2020)
Current antileishmanial drugs are toxic, expensive, and resistance to them has emerged. Several studies have focused on natural products as alternatives. In the present work, the chemical composition, in vitro antileishmanial activity, cytotoxicity effects, and the influence on mitochondrial function of the essential oil from Tagetes lucida Cav. was determined, as well its main compound estragole. Forty-nine compounds were detected in the oil by gas chromatography-mass spectrometry (GC-MS), of which estragole was the main constituent (97%). The oil showed inhibition of the promastigotes of L. tarentolae and L. amazonensis (IC50 = 61.4 and 118.8 µg/mL, respectively), decreased oxygen consumption of L. tarentolae, disrupted mitochondrial membrane potential in L. amazonensis, inhibitory activity on the intracellular amastigote of L. amazonensis (IC50 = 14.2 ± 1.6 µg/mL), and cytotoxicity values ranging from 80.8 to 156 µg/mL against murine macrophages and J774 cells. Estragole displayed higher activity on promastigotes (IC50 = 28.5 and 25.5 µg/mL, respectively), amastigotes (IC50 = 1.4 ± 0.1 µg/mL), and cytotoxicity values ranging from 20.6 to 14.5 µg/mL, respectively, while on mitochondria, it caused a decrease of the membrane potential but did not inhibit oxygen consumption. The potential antileishmanial activity of the essential oil from T. lucida and estragole makes these compounds favorable candidates for exploration in further studies.